2004
DOI: 10.1038/sj.ejcn.1601860
|View full text |Cite
|
Sign up to set email alerts
|

From milk to solids: a reference standard for the transitional eating process in infants and preschool children in Japan

Abstract: It seems appropriate to use this reference standard in the study of the transitional process from milk to solid food in infants and preschool children in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Our review found that many countries in the Asia Pacific region used rice porridge/cereal (See Table 4) for infants’ first foods since rice is culturally believed to help with digestion. Although some countries, including Japan, excluded this question for ethical reasons, other reports still described that the most common first solid foods was rice gruel [35,37]. These rice products are often of low energy and micronutrient density, including iron, zinc and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Our review found that many countries in the Asia Pacific region used rice porridge/cereal (See Table 4) for infants’ first foods since rice is culturally believed to help with digestion. Although some countries, including Japan, excluded this question for ethical reasons, other reports still described that the most common first solid foods was rice gruel [35,37]. These rice products are often of low energy and micronutrient density, including iron, zinc and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is substantial evidence that breastfeeding has a positive impact on masticatory function [5-7], this was the first study to show a positive association between the duration of breastfeeding and the quality of masticatory function in preschoolers with complete deciduous dentition. This association may be explained, at least in part, by the purported role of breastfeeding as a promoter of healthy development of the muscles later responsible for masticatory function, particularly the masseter muscles [5,6,21-23].…”
Section: Discussionmentioning
confidence: 99%
“…When performed correctly, it also plays a role in the development of the maxilla and mandible and contributed, together with genetic and environmental factors, to the stability of dental occlusion and functional and muscle balance. Whereas sucking at the breast has a favorable effect on masticatory function [5,7-9], other forms of sucking, such as those involved in bottle-feeding and pacifier use, produce different functional stimuli, which may jeopardize oral motor development and the position and strength of stomatognathic structures, with a detrimental impact on oral functions, including mastication [1,6,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…At 6 months soft meat is added to rice; fruit are also introduced. In Japan, rice is also commonly introduced first, but 100 days after birth, a traditional ceremony includes the introduction of fruit juice and vegetable soup (Inoue and Binns, 2014;Sakashita et al, 2004). Some mothers soften rice and meat by pre-mastication before feeding their infants (Jackson et al, 1992).…”
Section: Continuedmentioning
confidence: 99%